THE EFFECT OF WORK MOTIVATION AND WORK STRESS ON TEACHER PERFORMANCE - Rendy Rinaldy Saputra; Helda Rina; Jafar Sodiq (UIN Sumatera Utara Medan, 2019)
This study aims to determine the effect of work motivation and work stress on teacher performance at MIS Nurul Iman Sekincau, West Lampung. The approach used a quantitative approach by using Regressive analysis models to test hypotheses that have arranged, including 1) Motivation effected positive and significant on teacher performance, 2) Work stress had a positive and significant effect on teacher performance, and 3) Motivation and work stress had a positive and significant effect on teacher performance. The data were collected by conducting questionnaires with the number of questions 10 items for each variable to be examined. The collected data were analyzed and obtained results: 1) Motivation did not significantly influence performance, 2) Work stress significantly affected performance, and 3) Work motivation and work stress had a significant effect on performance.